Modified basalt fiber composite material, preparation method and PVC (polyvinyl chloride) material applying modified basalt fiber composite material
By modifying the chopped basalt fiber composite material, the problems of poor dispersion and insufficient thermal stability of basalt fibers in PVC materials are solved, and the thermal deformation temperature increase and application scope of PVC materials are achieved.
Patent Information
- Application Number
- CN202411856086.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, the poor dispersion of basalt fibers in polymer resin materials leads to poor processability and insufficient mechanical properties, and the inability to fully utilize the original advantages of the material, especially in PVC materials, there are problems such as insufficient thermal stability and use temperature limitations.
Modified chopped basalt fiber composite materials are used to improve the roughness of the fiber surface through acid and alkali treatment, graft stearate, and composite with thermoplastic acrylic resin, inorganic stabilizers and nano-silica components to form a synergistic stability system to enhance the thermal stability of PVC materials.
It significantly increases the thermal deformation temperature of PVC materials, extends the heat decomposition time, broadens the scope of application of materials, and improves mechanical properties and dispersion.
Smart Images

Figure BDA0005191840440000071 
Figure BDA0005191840440000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC material processing, and in particular to a modified basalt fiber composite material, a preparation method and a PVC material using the same. Background Art
[0002] Basalt fiber is a continuous fiber material made by melting natural basalt at 1450-1500℃ and then drawing it at high speed through a platinum-rhodium alloy wire drawing plate. Its main components are oxides such as silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, iron oxide and titanium dioxide. It has many properties such as high strength, electrical insulation, corrosion resistance and high temperature resistance. Therefore, it is widely used in many industries such as wall fireproof materials, fiber-reinforced composite materials, military protective materials, asphalt modified materials, etc. Basalt fibers that have not been surface-modified usually have poor dispersibility in polymer resin materials. Due to its insufficient affinity with the resin matrix, when preparing composite materials of basalt fibers and polymer resins, there are often problems such as poor processability, insufficient mechanical properties, and inability to give full play to the original advantages of the materials. At present, there have been many reports on the surface modification of basalt fiber materials, but there are few related research reports on the modification and processing of PVC material products using basalt fiber materials.
[0003] PVC (polyvinyl chloride) material is a general-purpose plastic with the highest production capacity in China. It is widely used in the fields of pipes, films, plates, profiles, etc. PVC material has the advantages of chemical corrosion resistance, wear resistance, electrical insulation, low water absorption, low cost, etc., but it also has the defects of easy decomposition at high temperature, low softening temperature, and long-term use temperature below 80°C, which limits its scope of use. To this end, the present invention aims to propose a modified basalt fiber composite material, a preparation method and a PVC material using the same, in order to solve the above technical problems. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects existing in the prior art and provide a modified basalt fiber composite material, a preparation method and a PVC material using the same. The modified basalt fiber composite material of the present invention is composited by modified short basalt fiber, thermoplastic acrylic resin, inorganic stabilizer, nano silicon dioxide and filler in a certain proportion, and can be directly put into the raw material formula of PVC material as an auxiliary agent for use, wherein the surface of the modified short basalt fiber is successively soaked in acid solution, washed with alkali solution and neutralized to improve the roughness of the surface of the short basalt fiber, so as to ensure that stearate is more easily, stably and evenly grafted on the surface of the short basalt fiber, and stearate itself can be used as a stabilizer of PVC material to absorb hydrogen chloride molecules generated when PVC resin is thermally decomposed, so in the PVC material added with the modified basalt fiber composite material of the present invention, the stearate grafted on the surface of the basalt fiber can form a synergistic stabilization system with the inorganic stabilizer in the PVC resin matrix to improve the thermal stability of the PVC material and prolong the thermal decomposition time of the PVC material. The preparation method of the modified basalt fiber composite material of the present invention has simple operation steps and high feasibility of application and implementation, which ensures that the modified basalt fiber composite material of the present invention can be smoothly prepared and implemented. The PVC material of the present invention significantly improves the heat deformation temperature compared with the traditional PVC material by adding an appropriate amount of the modified basalt fiber composite material, thereby broadening the application range of the PVC material.
[0005] One of the purposes of the present invention is to design a modified basalt fiber composite material, comprising the following weight components: 60-80 parts of modified chopped basalt fiber, 20-30 parts of thermoplastic acrylic resin, 1-5 parts of inorganic stabilizer, 0.1-1 part of nano-silicon dioxide, and 0-10 parts of filler, wherein the modified chopped basalt fiber is a chopped basalt fiber with stearate grafted on the surface.
[0006] A preferred technical solution is that the diameter of the modified chopped basalt fiber is 6 to 22 μm.
[0007] Another preferred technical solution is that the thermoplastic acrylic resin has an intrinsic viscosity of 0.5 to 12 and a weight average molecular weight of 500,000 to 2.5 million.
[0008] Another preferred technical solution is that the inorganic stabilizer is one or more of magnesium aluminum hydrotalcite, porous zeolite, and activated carbon.
[0009] Another preferred technical solution is that the filler is one or more of calcium carbonate, talcum powder, mica powder, zeolite, kaolin, and montmorillonite.
[0010] The second object of the present invention is to provide a method for preparing the modified basalt fiber composite material, comprising the following steps:
[0011] S1: Soak the chopped basalt fibers in deionized water for 4 to 6 hours to remove surface oil and impurities;
[0012] S2: Take out the chopped basalt fibers from the deionized water, place them in an acidic solution, and soak them under stirring for 2 to 4 hours at a certain temperature;
[0013] S3: filtering the acid solution from the chopped basalt fibers soaked in the acid solution, washing the chopped basalt fibers with deionized water until the pH of the deionized water after washing is 6 to 7, and then drying the washed chopped basalt fibers;
[0014] S4: placing chopped basalt fibers, deionized water, xylene, and stearate in a reaction container according to a certain weight ratio, and stirring the reaction at a certain temperature for 4 to 6 hours;
[0015] S5: After the reaction in step S4 is completed, the reaction mixture is filtered, and the solid fiber is washed with an alkaline solution of a certain concentration until the pH of the alkaline solution after washing is 8-10, and the solid fiber is dried to obtain modified chopped basalt fiber;
[0016] S6: 60-80 parts of modified chopped basalt fibers, 20-30 parts of thermoplastic acrylic resin, 1-5 parts of inorganic stabilizer, 0.1-1 part of nano-silicon dioxide, and 0-10 parts of filler are placed in a mixer, and mixed evenly at high speed under certain temperature conditions to obtain a modified basalt fiber composite material.
[0017] The preferred technical solution is that in the step S2, the acidic solution used is one of sulfuric acid, hydrochloric acid and nitric acid, and the mass concentration of the acidic solute in the acidic solution is 10-20%, and the immersion temperature of the chopped basalt fiber in the acidic solution is 50-70°C; in the step S3, the cleaned chopped basalt fiber is baked in an oven at a temperature of 80-105°C for 0.5-1h until dry; in the step S4, the mass feed ratio of chopped basalt fiber, deionized water, xylene and stearate is 1:10:5:1, and the reaction is carried out. The temperature is 60-80°C, and the stearate used is one of zinc stearate and calcium stearate; in the step S5, the alkaline solution used is one of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and calcium hydroxide aqueous solution, and the mass concentration of the alkaline solute in the alkaline solution is 5-10%, and the solid fiber is baked in an oven at a temperature of 60-100°C for 12-24 hours until it is dry; in the step S6, the mixing temperature is 60-80°C, the mixer speed is 500-800r / min, and the mixing time is 30-60min.
[0018] The third object of the present invention is to provide a PVC material, wherein the PVC material contains the modified basalt fiber composite material, and the added amount of the modified basalt fiber composite material is 5 to 30 parts based on 100 parts of PVC resin.
[0019] The advantages and beneficial effects of the present invention are:
[0020] 1. A modified basalt fiber composite material of the present invention is composited by modified short basalt fiber, thermoplastic acrylic resin, inorganic stabilizer, nano silicon dioxide and filler in a certain proportion, and can be directly added to the raw material formula of PVC material as an auxiliary agent for use, wherein the surface of the modified short basalt fiber is successively soaked in acid solution, cleaned and neutralized with alkali solution to improve the roughness of the surface of the short basalt fiber, so as to ensure that stearate is more easily, stably and evenly grafted on the surface of the short basalt fiber, and stearate itself can be used as a stabilizer of PVC material to absorb hydrogen chloride molecules generated when PVC resin is thermally decomposed, and the special porous structure and layered structure of the inorganic stabilizer can also absorb hydrogen chloride molecules. When the hydrogen chloride molecules are absorbed, the number of active hydrogen chloride molecules participating in the chain decomposition reaction of the PVC resin molecular chain is reduced, so in the PVC material added with the modified basalt fiber composite material of the present invention, the stearate grafted on the surface of the basalt fiber can form a synergistic stabilization system with the inorganic stabilizer in the PVC resin matrix to improve the thermal stability of the PVC material and prolong the thermal decomposition time of the PVC material.
[0021] 2. A modified basalt fiber composite material of the present invention has improved dispersibility of the modified chopped basalt fiber material as a rigid material in the PVC matrix due to the grafting of stearate on the surface of the modified chopped basalt fiber and compounding with thermoplastic acrylic resin. The PVC material added with the modified basalt fiber composite material of the present invention significantly improves its heat deformation temperature, so that the PVC material can be used for a long time at a higher temperature; the thermoplastic acrylic resin is a high molecular weight thermoplastic resin, and the molecular chain contains an ester group, which has good affinity and compatibility with the PVC resin, and has affinity with stearate, so that the long molecular chain of the thermoplastic acrylic resin can be compatible with the PVC resin and can be more easily wrapped on the surface of the modified basalt fiber material, forming a ternary compatible system of PVC resin, modified basalt fiber, and thermoplastic acrylic resin, wherein the modified basalt fiber material acts as a rigid skeleton and plays a supporting role in the process of thermal deformation of the PVC resin. Therefore, the PVC resin material will deform at a higher use temperature, thereby widening and improving its use temperature.
[0022] 3. The preparation method of a modified basalt fiber composite material of the present invention has simple operation steps and high feasibility of application and implementation, ensuring that the modified basalt fiber composite material of the present invention can be smoothly prepared and implemented.
[0023] 4. The PVC material of the present invention significantly improves the heat deformation temperature compared with the traditional PVC material by adding an appropriate amount of modified basalt fiber composite material, thereby broadening the application range of the PVC material. DETAILED DESCRIPTION
[0024] The specific implementation of the present invention is further described below in conjunction with the examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.
[0025] Example 1
[0026] A modified basalt fiber composite material comprises the following weight components: 60 parts of modified short-cut basalt fiber, 20 parts of thermoplastic acrylic resin, 1 part of magnesium-aluminum hydrotalcite, and 0.1 part of nano-silicon dioxide. The modified short-cut basalt fiber is a short-cut basalt fiber with stearate grafted on the surface.
[0027] Preferably, the diameter of the modified chopped basalt fiber is 6-22 μm; the intrinsic viscosity of the thermoplastic acrylic resin is 0.5-12, and the weight average molecular weight ranges from 500,000 to 2.5 million.
[0028] The preparation method of the modified basalt fiber composite material comprises the following steps:
[0029] S1: Soak the chopped basalt fibers in deionized water for 4 h to remove surface oil and impurities;
[0030] S2: The chopped basalt fibers were taken out from the deionized water and placed in a 10% sulfuric acid solution, and stirred and soaked at 50°C for 4 hours;
[0031] S3: filtering the sulfuric acid solution from the chopped basalt fibers soaked in the sulfuric acid solution, washing the chopped basalt fibers with deionized water until the pH of the deionized water after washing is 6-7, and then baking the washed chopped basalt fibers in an oven at 80° C. for 1 hour until dry;
[0032] S4: short basalt fiber, deionized water, xylene and stearate are placed in a reaction vessel in a mass ratio of 1:10:5:1, and stirred for reaction at 60°C for 4 hours;
[0033] S5: After the reaction in step S4 is completed, the reaction mixture is filtered, and the solid fiber is washed with a calcium hydroxide solution with a mass concentration of 5% until the pH of the calcium hydroxide solution after washing is 8-10, and the solid fiber is baked in an oven at a temperature of 60° C. for 24 hours until dry, to obtain modified chopped basalt fiber;
[0034] S6: 60 parts of modified chopped basalt fiber, 20 parts of thermoplastic acrylic resin, 1 part of magnesium aluminum hydrotalcite, and 0.1 parts of nano-silicon dioxide are placed in a mixer, and mixed at a high speed of 60° C. and 500 r / min for 60 minutes to obtain a modified basalt fiber composite material.
[0035] Example 2
[0036] A modified basalt fiber composite material comprises the following components by weight: 70 parts of modified short-cut basalt fiber, 25 parts of thermoplastic acrylic resin, 3 parts of porous zeolite, 0.5 parts of nano-silicon dioxide and 5 parts of calcium carbonate. The modified short-cut basalt fiber is a short-cut basalt fiber with stearate grafted on the surface.
[0037] Preferably, the diameter of the modified chopped basalt fiber is 6-22 μm; the intrinsic viscosity of the thermoplastic acrylic resin is 0.5-12, and the weight average molecular weight ranges from 500,000 to 2.5 million.
[0038] The preparation method of the modified basalt fiber composite material comprises the following steps:
[0039] S1: Soak the chopped basalt fibers in deionized water for 6 hours to remove surface oil and impurities;
[0040] S2: Take out the short basalt fibers from the deionized water, place them in a nitric acid solution with a mass concentration of 15%, and soak them at 70°C for 2 hours with stirring;
[0041] S3: filtering the sulfuric acid solution from the chopped basalt fibers soaked in the sulfuric acid solution, washing the chopped basalt fibers with deionized water until the pH of the deionized water after washing is 6-7, and then baking the washed chopped basalt fibers in an oven at 100° C. for 40 minutes until dry;
[0042] S4: short basalt fiber, deionized water, xylene and stearate are placed in a reaction vessel in a mass ratio of 1:10:5:1, and stirred for reaction at 80°C for 5 hours;
[0043] S5: After the reaction in step S4 is completed, the reaction mixture is filtered, and the solid fiber is washed with a sodium hydroxide solution with a mass concentration of 8% until the pH of the calcium hydroxide solution after washing is 8-10, and the solid fiber is baked in an oven at a temperature of 80° C. for 18 hours until dry, to obtain modified chopped basalt fiber;
[0044] S6: 70 parts of modified chopped basalt fibers, 25 parts of thermoplastic acrylic resin, 3 parts of porous zeolite, 0.5 parts of nano-silicon dioxide, and 5 parts of calcium carbonate were placed in a mixer, and mixed at a high speed of 70° C. and 600 r / min for 45 minutes to obtain a modified basalt fiber composite material.
[0045] Example 3
[0046] A modified basalt fiber composite material comprises the following components by weight: 80 parts of modified short-cut basalt fiber, 30 parts of thermoplastic acrylic resin, 5 parts of activated carbon, 1 part of nano-silicon dioxide, 5 parts of mica powder and 5 parts of zeolite. The modified short-cut basalt fiber is a short-cut basalt fiber with stearate grafted on the surface.
[0047] Preferably, the diameter of the modified chopped basalt fiber is 6-22 μm; the intrinsic viscosity of the thermoplastic acrylic resin is 0.5-12, and the weight average molecular weight ranges from 500,000 to 2.5 million.
[0048] The preparation method of the modified basalt fiber composite material comprises the following steps:
[0049] S1: Soak the chopped basalt fibers in deionized water for 5 h to remove surface oil and impurities;
[0050] S2: Take out the short chopped basalt fibers from the deionized water, place them in a hydrochloric acid solution with a mass concentration of 20%, and soak them at 60°C for 3 hours with stirring;
[0051] S3: filtering the sulfuric acid solution from the chopped basalt fibers soaked in the sulfuric acid solution, washing the chopped basalt fibers with deionized water until the pH of the deionized water after washing is 6-7, and then baking the washed chopped basalt fibers in an oven at 105° C. for 30 minutes until dry;
[0052] S4: short basalt fiber, deionized water, xylene and stearate are placed in a reaction vessel in a mass ratio of 1:10:5:1, and stirred for reaction at 70°C for 6 hours;
[0053] S5: After the reaction in step S4 is completed, the reaction mixture is filtered, and the solid fiber is washed with a potassium hydroxide solution with a mass concentration of 10% until the pH of the calcium hydroxide solution after washing is 8-10, and the solid fiber is baked in an oven at a temperature of 100° C. for 12 hours until dry, to obtain modified chopped basalt fiber;
[0054] S6: 80 parts of modified chopped basalt fiber, 30 parts of thermoplastic acrylic resin, 5 parts of activated carbon, 1 part of nano-silicon dioxide, 5 parts of mica powder, and 5 parts of zeolite are placed in a mixer, and mixed at a high speed of 80° C. and 800 r / min for 30 minutes to obtain a modified basalt fiber composite material.
[0055] Test experiment:
[0056] In order to more clearly illustrate the beneficial effects of the modified basalt fiber composite material of the present invention in the application of PVC material, the modified basalt fiber material of the present invention is added as an additive to the PVC material formula to prepare a PVC material and used as a test example, wherein the PVC material formula in Test Example 1 adopts the modified basalt fiber composite material in Example 1, the PVC material formula in Test Example 2 adopts the modified basalt fiber composite material in Example 2, and the PVC material formula in Test Example 3 adopts the modified basalt fiber composite material in Example 3; the present invention also provides a PVC material without adding modified basalt fiber and a PVC material with adding unmodified chopped basalt fiber material as comparative examples, wherein the PVC material formula compositions of Test Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 1 below:
[0057] Table 1 Formulas of PVC materials in Test Examples 1 to 3 and Comparative Examples 1 to 2
[0058] Test Example 1 Test Example 2 Test Example 3 Comparative Example 1 Comparative Example 2 PVC resin 100 100 100 100 100 Environmentally friendly stabilizer 5 5 5 5 5 Lubricants 1 1 1 1 1 Unmodified basalt fiber - - - - 17 Modified basalt fiber 5 17 30 - -
[0059] Test Examples 1 to 3 and Comparative Examples 1 to 2 were processed into PVC material samples according to the formula in Table 1. The Vicat softening temperature of the PVC material samples was tested according to the test method specified in GB1633-79 "Thermoplastic Softening Point (Vicat) Test Method". The test results are shown in Table 2 below:
[0060] Table 2 Vicat softening temperature of PVC material samples in test examples 1 to 3 and comparative examples 1 to 2
[0061]
[0062] The experimental result data in Table 2 show that when the modified basalt fiber composite material of the present invention is added as an auxiliary agent to the PVC material formula, the Vicat softening temperature of the PVC material is significantly improved compared with Comparative Example 1 without the modified basalt fiber composite material and Comparative Example 2 with the unmodified basalt fiber composite material, that is, the heat-resistant deformation temperature of the PVC material is significantly improved, thereby helping to broaden the application scope of the PVC material.
[0063] Test Examples 1 to 3 and Comparative Examples 1 to 2 were processed into PVC material samples according to the formula in Table 1. The thermal stability time of the PVC material samples was tested according to the test method specified in GB2917-1982 "Test Method for Thermal Stability of Polyvinyl Hydrogen - Congo Red Method and pH Method". The test results are shown in Table 3 below:
[0064] Table 3 Thermal stability time of PVC material samples in test examples 1 to 3 and comparative examples 1 to 2
[0065]
[0066] The experimental result data in Table 3 show that when the modified basalt fiber composite material of the present invention is added as an auxiliary agent to the PVC material formula, the Congo red discoloration time of the PVC material is significantly prolonged compared with the comparative example 1 without adding the modified basalt fiber composite material and the comparative example 2 with adding the unmodified basalt fiber composite material, that is, the thermal stability of the PVC material is significantly improved, which helps to broaden the application scope of the PVC material and achieve the purpose of the invention.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified basalt fiber composite material, characterized in that: The invention comprises the following components by weight: 60-80 parts of modified short-cut basalt fiber, 20-30 parts of thermoplastic acrylic resin, 1-5 parts of inorganic stabilizer, 0.1-1 parts of nano silicon dioxide and 0-10 parts of filler. The modified short-cut basalt fiber is short-cut basalt fiber with stearate grafted on the surface.
2. The modified basalt fiber composite material according to claim 1, characterized in that: The diameter of the modified short-cut basalt fiber is 6-22 μm.
3. The modified basalt fiber composite material according to claim 1, characterized in that: The intrinsic viscosity of the thermoplastic acrylic resin is 0.5-12, and the weight average molecular weight ranges from 500,000 to 2.5 million.
4. The modified basalt fiber composite material according to claim 1, characterized in that: The inorganic stabilizer is one or more of magnesium aluminum hydrotalcite, porous zeolite and activated carbon.
5. The modified basalt fiber composite material according to claim 1, characterized in that: The filler is one or more of calcium carbonate, talcum powder, mica powder, zeolite, kaolin and montmorillonite.
6. The method for preparing the modified basalt fiber composite material according to any one of claims 1 to 5, characterized in that: The steps are as follows: S1: Soak the chopped basalt fibers in deionized water for 4 to 6 hours to remove surface oil and impurities; S2: Take out the chopped basalt fibers from the deionized water, place them in an acidic solution, and soak them under stirring for 2 to 4 hours at a certain temperature; S3: filtering the acid solution from the chopped basalt fibers soaked in the acid solution, washing the chopped basalt fibers with deionized water until the pH of the deionized water after washing is 6 to 7, and then drying the washed chopped basalt fibers; S4: placing chopped basalt fibers, deionized water, xylene, and stearate in a reaction container according to a certain weight ratio, and stirring the reaction at a certain temperature for 4 to 6 hours; S5: After the reaction in step S4 is completed, the reaction mixture is filtered, and the solid fiber is washed with an alkaline solution of a certain concentration until the pH of the alkaline solution after washing is 8-10, and the solid fiber is dried to obtain modified chopped basalt fiber; S6: 60-80 parts of modified chopped basalt fibers, 20-30 parts of thermoplastic acrylic resin, 1-5 parts of inorganic stabilizer, 0.1-1 part of nano-silicon dioxide, and 0-10 parts of filler are placed in a mixer, and mixed evenly at high speed under certain temperature conditions to obtain a modified basalt fiber composite material.
7. The method for preparing the modified basalt fiber composite material according to claim 6, characterized in that: In the step S2, the acidic solution used is one of sulfuric acid, hydrochloric acid and nitric acid, and the mass concentration of the acidic solute in the acidic solution is 10-20%, and the immersion temperature of the chopped basalt fiber in the acidic solution is 50-70°C; in the step S3, the cleaned chopped basalt fiber is baked in an oven at 80-105°C for 0.5-1h until dry; in the step S4, the mass feed ratio of chopped basalt fiber, deionized water, xylene and stearate is 1:10:5:1, and the reaction temperature is 60 ~80℃, the stearate used is one of zinc stearate and calcium stearate; in the step S5, the alkaline solution used is one of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution and calcium hydroxide aqueous solution, and the mass concentration of the alkaline solute in the alkaline solution is 5-10%, and the solid fiber is baked in an oven at a temperature of 60-100℃ for 12-24h until dry; in the step S6, the mixing temperature is 60-80℃, the mixer speed is 500-800r / min, and the mixing time is 30-60min.
8. A PVC material, characterized in that: The PVC material contains the modified basalt fiber composite material according to any one of claims 1 to 5, and the added amount of the modified basalt fiber composite material is 5 to 30 parts based on 100 parts of PVC resin.